2009
DOI: 10.1080/09553000903009522
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive 50 Hz pulsed electromagnetic field ameliorates the diabetes-induced impairments in the relaxation response of rat thoracic aorta rings

Abstract: Diabetes reduced the relaxation response of thoracic aorta rings. It also affected the membrane potentials of the rings. Treatment with PEMF ameliorated the diabetes-induced impairments in the relaxation response of these rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This finding supports the hypothesis that the involvement of K + channels in ACh relaxation is inhibited by diabetes. Our results are consistent with those obtained previously in aorta where diabetes was found to inhibit the vasodilation mediated by K Ca or Kv channels (Malakul et al 2008;Kavak et al 2009;Wang et al 2012a). Furthermore, since diabetes-induced decrease in β-adrenoceptormediated vascular dilatation has been shown to be primarily associated with endothelium-independent mechanisms, our findings, which show a decrease in salbutamol relaxation in YD rats, can be explained by the dysfunction of KCa or Kv (Karasu et al 1997b;Ferro et al 2004;Chai et al 2005;Ko et al 2008).…”
Section: Discussionsupporting
confidence: 94%
“…This finding supports the hypothesis that the involvement of K + channels in ACh relaxation is inhibited by diabetes. Our results are consistent with those obtained previously in aorta where diabetes was found to inhibit the vasodilation mediated by K Ca or Kv channels (Malakul et al 2008;Kavak et al 2009;Wang et al 2012a). Furthermore, since diabetes-induced decrease in β-adrenoceptormediated vascular dilatation has been shown to be primarily associated with endothelium-independent mechanisms, our findings, which show a decrease in salbutamol relaxation in YD rats, can be explained by the dysfunction of KCa or Kv (Karasu et al 1997b;Ferro et al 2004;Chai et al 2005;Ko et al 2008).…”
Section: Discussionsupporting
confidence: 94%
“…A study on Wistar rats [15] with streptozotocin-induced diabetes mellitus revealed that repetitive pulsed magnetic field (50 Hz, 5 mT) ameliorated the diabetes-induced macroangiopathy. Diabetic rats treated with pulsed magnetic field showed an increase in thoracic aorta relaxation response to acetylcholine and reduced contraction response to phenylephrine compared to the diabetic but non-exposure group.…”
Section: Magnetic Field (Magnetotherapy and Magnetostimulation)mentioning
confidence: 99%
“…The MF was generated in a specially designed device that had a solenoid 500 mm in length and 210 mm in diameter. This magnet was constructed by winding 1400 turns of an insulated soft copper wire, which was 1.4 mm in diameter, on a fiber base (19,20). A MF intensity of B = 5 mT was measured inside the solenoid using a digital teslameter (Phywe, Gottingen, Germany) with an axial Hall probe (Phywe).…”
Section: Magnetic Field Exposurementioning
confidence: 99%